Mental alertness and flexibility and psychological flow of the student Counseling in Tarif governorate, Saudi Arabia- A comparative study between the new and old mentors - Al Ruwaili, Al Nashmi Bashir (Journal of Educational and Psychological Sciences, 2019)
The aim of this study was to determine the level of mental alertness, psychological flow and psychological flexibility of the student guides in Tarif governorate, and to determine the nature of the relationship between mental alertness, psychological flow and psychological flexibility of the student mentors and to verify differences in mental alertness, psychological flow and psychological flexibility of the student guides in the region Tarif Governorate according to years of experience, All members of the study community were from the city of Arar, 30 and the mental alert scale was used for the Philadelphia Mindfulness Scale (PHLMS) mentors, the ego- elasticity of the student Counseling for Fahan (2010) for ego elasticity, Instructors students. For Jackson and Marshall, 1996, translated by Mahadin (2014), the results of the study found that the student Counseling in the level of mental alertness and elasticity of the Anna and the flow of psychological was an average level, indicating that the mentors students have a moderate degree of mental alertness and flexibility and self- flow The relationship was statistically significant and positive, and there were no differences between the Counseling and the student Counseling in Tarif governorate due to the variable of experience whether in mental alertness, psychological flexibility or psychological flow. The study of some of the recommendations and most important attention to the positive psychological variables among the student Counseling.